Percepção viso-motora de escolares com Transtorno do Déficit de Atenção com Hiperatividade - Germano, Giseli Donadon [UNESP]; Pinheiro, Fábio Henrique [UNESP]; Okuda, Paola Matiko Martins [UNESP]; Capellini, Simone Aparecida [UNESP] (Sociedade Brasileira de Fonoaudiologia, 2013)
PURPOSE: The aim of this study was to characterize and to compare the visual-motor perception of students with Attention Deficit with Hyperactivity Disorder (ADHD) with students with good academic performance. METHODS: Forty students from 2nd to 5th grades of an elementary public school, male gender (100%), aged between 7 and 10 years and 8 months old participated, divided into: GI (20 students with ADHD) and GII (20 students with good academic performance), paired according to age, schooling and gender with GI. The students were submitted to Developmental Test of Visual Perception (DTVP-2). RESULTS: The students of GI presented low performance in spatial position and visual closure (reduced motor) and inferior age equivalent in reduced motor perception, when compared to GII. CONCLUSION: The difficulties in visual-motor perception presented by students of GI cannot be attributed to a primary deficit, but to a secondary phenomenon of inattention that interferes directly in their visual-motor performance.

OBJETIVO: Caracterizar e comparar as habilidades de percepção viso-motoras de escolares com Transtorno do Déficit de Atenção com Hiperatividade (TDAH) com escolares com bom desempenho acadêmico. MÉTODOS: Participaram deste estudo 40 escolares na faixa etária de 7 anos a 10 anos e 8 meses, do 2º ao 5º ano do Ensino Fundamental de escolas públicas, divididos em GI (20 escolares com diagnóstico interdisciplinar de TDAH) do gênero masculino (100%) e GII (20 escolares com bom desempenho escolar), pareados com o GI em idade, escolaridade e gênero. Os escolares foram submetidos ao Teste Evolutivo de Percepção Visual (DTVP-2). RESULTADOS: Os escolares de GI apresentaram desempenho inferior na função de posição no espaço e closura visual (motricidade reduzida) e equivalente de idade inferior para percepção de motricidade reduzida em relação ao GII. CONCLUSÃO: As dificuldades em percepção viso-motora apresentadas pelos escolares de GI podem ser atribuídas não a um déficit primário, mas a um fenômeno secundário à desatenção que interfere de forma direta em seu desempenho de percepção viso-motora.
Visual-motor perception in students with Attention Deficit with Hyperactivity Disorder
Keywords: Transtorno do déficit de atenção com hiperatividade; Percepção visual; Destreza motora; Avaliação; Educação; Attention deficit disorder with hyperactivity; Visual perception Motor skills; Evaluation; Education